2013
DOI: 10.1111/bph.12154
|View full text |Cite
|
Sign up to set email alerts
|

Roles of basophils and mast cells infiltrating the lung by multiple antigen challenges in asthmatic responses of mice

Abstract: BACKGROUND AND PURPOSEMast cell hyperplasia has been observed in the lungs of mice with experimental asthma, but few reports have studied basophils. Here, we attempted to discriminate and quantify mast cells and basophils in the lungs in a murine asthma model, determine if both cells were increased by multiple antigen challenges and assess the roles of those cells in asthmatic responses. EXPERIMENTAL APPROACHSensitized Balb/c mice were intratracheally challenged with ovalbumin four times. Mast cells and basoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 50 publications
1
22
0
3
Order By: Relevance
“…Depletion of basophils with MAR‐1 may affect mast cells . To further confirm the key role of basophils in the Th2 immune response, adoptive transfer of basophils to naive BALB/c mice was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of basophils with MAR‐1 may affect mast cells . To further confirm the key role of basophils in the Th2 immune response, adoptive transfer of basophils to naive BALB/c mice was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies secreted from plasma cells bind to the high affinity FcεRI on mast cells. On subsequent exposure to allergens, antibodies bound to FcεRI on mast cells cross-link causing a signal transduction leading to the activation of mast cells releasing pre-formed mediators from their granules together with many newly formed mediators [130,131]. Molecular signals to reduce the activation of mast cells can be promising to control inflammatory response.…”
Section: Interaction Of Dcs With Various Immune Cellsmentioning
confidence: 99%
“…Unlike histamine and PAF, tryptase reaches peak concentrations ∼30-60 minutes after allergy onset, has a serum half-life of 90 minutes, and exhibits low serum concentrations in normal, nonallergic individuals (Laroche et al, 1991). Although other studies have suggested that histamine levels may be a more useful immediate (e.g., 10 minutes) indicator of the onset of allergies compared with the release of mast cell proteases in mice (Nabe et al, 2013), a biomarker of allergy that is elevated and stable for several hours after an allergic reaction may be more useful as an eventual clinical biomarker of asparaginase-induced allergies. Taken together, our results suggest that tryptase may be a possible clinical biomarker for confirming episodes of hypersensitivity to asparaginase.…”
mentioning
confidence: 99%